Implementation of Multidimensional Enterprise Architecture for Optimizing Suka Nanti Village-Owned Enterprises - Repaldo; Yogi Isro Mukti; Risnaini Masdalipa (Jurnal Teknologi Informatika dan Komputer, 2026)
The problems faced by BUMDes Suka Nanti in developing its Bottled Drinking Water (AMDK) business are the lack of structured and integrated business planning, where business processes are still conventional, data management has not been well documented, and the use of technology is limited, potentially causing operational inefficiencies and unclear financial management. This study aims to develop a business plan and blueprint for developing BUMDes AMDK using the Integrated Multidimensional Enterprise Architecture (idEA) approach and analyze its readiness for implementation through a SWOT analysis. The research method is carried out by analyzing the current business process to identify weaknesses, then modeling new business processes using the idEA approach that includes business architecture, data, applications, and technology, and is complemented by a SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats of implementing the blueprint. The results of the study indicate that the idEA approach produces an integrated and applicable AMDK business process blueprint, while the SWOT analysis shows that the design has strong potential to be implemented with the right strategy to improve operational efficiency, financial transparency, and support BUMDes Suka Nanti to become a modern and sustainable business. By implementing Integrated Multidimensional Enterprise Architecture (idEA), a blueprint was designed that includes mapping the dimensions of business, data, applications, and technology. This can serve as a strategic guide for the planning, implementation, and operational evaluation of the Suka Nanti Village-Owned Enterprise (BUMDes).